PENERAPAN STRATEGI PEMBELAJARAN AKTIF ROTATING TRIO EXCHANGE (RTE) DISERTAI MEDIA QUESTION BOX DAPAT MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN LAJU REAKSI DI KELAS XI IPA SMA NEGERI 2 PEKANBARU - Riza, Shinta Riza; Rery, R Usman Rery; ', Abdullah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aimed at investigating the significant difference of students’ learning achievement between students taught using Rotating Trio Exchange(RTE) assisted with question box and students taught conventionally with question box in chemistry subject at SMAN 2 Pekanbaru. Subject of this research were students at XI MIA 3 as experiment class and XI MIA 1 as control class were randomely selected. Data analized after giving pretest and postest to each class by using ttest. The results revealed that application active learning strategy of RTE was capable to improve student’s achievement in chemistry especially in Reaction Rate Subject at 11th SMAN 2 Pekanbaru. The result of the study shows a significant difference of students’ learning achievement between students taught using RTE assisted with questions box and students taught conventionally with question box with tobserved 3,87 >  ttabel 1,67. And n-gain score for exsperiment class is 0.65 and control class is  0.47, means the improvement of both classes achievement was in average category. Key Words : Rotating Trio Exchange, RTE, Question Box, Students’ Achievment, Reacction Rate